KAJIAN METODA PELAKSANAAN PEKERJAAN PONDASI BORED PILE PADA TAHAP PERENCANAAN PELAKSANAAN - Putu Panji Tresna Gita; I Made Satria Dharmayoga; I Wayan Jawat (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2020)
Bored pile foundation is a pile foundation whose installation is done by drilling the soil first. This type of bored pile foundation is widely used in construction projects. The selected bore pile foundation is adjusted to the type of soil, terrain conditions, and the selected construction method. The construction method is the elaboration of procedures and works implementation techniques which are the core of all activities in the construction management system. For this reason, it is interesting to study the method of implementing the bore pile foundation at the planning stage of the implementation of the GOR Development project in Abiansemal, Badung. The implementation planning stage is an important activity in order to provide a more detailed picture of strategies and techniques for working efficiently and effectively in terms of time, quality and cost. The goal to be achieved in this research is to study the method of implementing the foundation at the planning stage of implementation. So that it can contribute to the development of knowledge about the application of the theory of the method of implementing the bore pile foundation and is information for those who are interested in further research. Based on the results of the study that the preparatory work begins with the determination of the pile center point and placement of bored pile devices. In drilling work using the wet drilling method volume 1105.00 m with a duration of 8 days. For the work of reinforcing the volume of 9309.61 kg and the duration of 13 days was preceded by the fabrication process and continued with the installation of reinforcement into the borehole. Casting is done using a pipe, volume 74.394 m³ with a duration of 11 days. Next, determine the pile cap and excavation work, followed by pile cap floor work with concrete fillings, volume 136.708 m³ for 6 days. As formwork using concrete blocks with a volume of 237.474 m² worked on for 14 days, followed by the formation of reinforcement and assembly of volume 5454.21 kg with a duration of 9 days and casting methods carried out manually with a volume of 117.632 m³ and a duration of 14 days.